Shoot feeding period characterization of the pistachio twig borer - Braham M. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
In Tunisia, The pistachio twig borer, Chaetoptelius vestitus Mulsant & Rey (Coleoptera, Curculionidae, Scolytinae) is a serious pest of pistachio tree, Pistacia vera. The insect has two dispersal phases: in the first, mature adults seek recently cut pistachio branches, or live tree branches weakened by drought or physiologically stressed to lay eggs and initiate reproduction; in the second, new emerged adults fly toward healthy trees where they feed on the buds and excavate feeding galleries just beneath the buds toward the center of the twig. This paper deals with a study over two successive years conducted in the field in the Centre-East of Tunisia on shoot feeding, overwintering and the presence of C. vestitus inside pistachio twigs. The duration of these processes including age, diameter, length, of the burrowed tunnels as well as degree of shoot infestation were reported. The sampled twigs varied from 1 to 53 cm in length and between 0.2 and 1.1 cm in section. Results indicated that the percentage of the shoots damaged by C. vestitus ranged from 70 to 100% all year round except during the period from late March to late April where the percentage of infestation varied from 15 to 25%. This period could be attributed to the swarming of adults emerged from reproduction sites. Adults are present in feeding galleries all year round. However their densities dramatically decrease from late October to late March from an average of 16 adults per meter of twigs to 4 adults. This period could be a sign of adult migration as demonstrated the low number of adults per gallery; an average of 0.2 adult per gallery compared with an average of 0.8 adult per gallery throughout the other period. Most adults were found in feeding tunnels in current-year shoots. The length of feeding galley varied from 0.03 cm to 2.75 cm and diameter varied from 0.2 cm to 1.1 cm. The mean number of adults per meter of twigs varied from 0 to 68.18 depending on sampling dates. Consequently, the insect overwinters in two forms (1) a portion of the population hibernate as adult stage inside feeding galleries of pistachio shoots and (2) the other fraction leaves feeding galleries in autumn to initiate reproduction phase. The knowledge of shoot-feeding phase is one of the main elements when developing integrated management strategies.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)